Spinal Dural Arteriovenous Fistula: Diagnosis and Treatment - Nur Setiawan Suroto (Neurologico Spinale Medico Chirurgico, 2018)
Spinal dural arteriovenous (AV) fistulas are the most commonly encountered vascular malformation of the spinal cord and a treatable cause for progressive paraplegia or tetraplegia. They most commonly affected are elderly men and are classically found in the thoracolumbar region. Symptoms gradually progress or decline in a stepwise manner and are commonly associated with pain and sphincter disturbances. Surgical or endovascular disconnection of the fistula has a high success rate with a low rate of morbidity. Motor symptoms are most likely to improve after treatment, followed by sensory disturbances, and lastly sphincter disturbances.